Services-Led Growth Better Prospects after the Pandemic? - Nayyar, Gaurav (The World Bank, 2023)
The service sector accounted for two-thirds of economic growth in emerging market and developing economies over the past three decades. It consists of a wide range of activities, ranging from high-skilled offshorable services, such as information and communications technology (ICT) and professional services, to low-skilled "contact" services, such as retail and hospitality. The pandemic disrupted many low-skilled contact services that typically require face-to-face interactions between providers and consumers. High-skilled offshorable services were the least affected owing to the use of digital technology that enabled remote delivery. Increased digitalization has improved prospects for scale economies and innovation in the service sector that were previously constrained by the need for physical proximity and the lack of opportunities to augment labor with capital. Policies to support the diffusion of digital technologies could therefore further raise the growth potential of the service sector. Policies to improve market access for, and skills in, ICT and professional services could ease important constraints on growth opportunities in these high-skilled offshorable services that have best withstood the pandemic. The same holds true for policies, including regulatory reforms, that promote investment in low-skilled contact services, such as transportation, which have important linkages with the wider economy
Keywords: COVID-19 Pandemic Impact on Service Sector; Digitalization; Emerging Market Growth; Growth; Health, Nutrition and Population; Market Access Policy; Offshoring Services; Service Sector